Body mass index, serum total cholesterol, and risk of gastric high-grade dysplasia: A case–control study among Chinese adults. Issue 35 (August 2016) - Huang, Ya-Kai; Kang, Wei-Ming; Ma, Zhi-Qiang; Liu, Yu-Qin; Zhou, Li; Yu, Jian-Chun
Abstract : Abstract: Obesity is related to an increased risk of gastric cardia cancer. However, the influences of excess body weight and serum total cholesterol on the risk of gastric high-grade dysplasia have not been fully characterized. A case–control study was conducted to explore the relationships between body mass index (BMI), serum total cholesterol level, and the risk of gastric high-grade dysplasia in Chinese adults. A total of 893 consecutive patients with gastric high-grade dysplasia (537 men and 356 women) and 902 controls (543 men and 359 women) were enrolled from January 2000 to October 2015. Odds ratios (ORs) with 95% confidence intervals (CIs) were estimated, and a multivariate analysis was conducted. After adjusting for age, alcohol consumption, smoking status, family history of gastric cancer or esophageal cancer, and serum total cholesterol level, a BMI ranging from 27.5 to 29.9 was significantly related to an increased risk of gastric high-grade dysplasia in both men (adjusted OR = 1.87, 95% CI = 1.24–2.81) and women (adjusted OR = 2.72, 95% CI = 1.44–5.16). The 2 highest BMI categories (27.5–29.9 and ≥30.0) were identified as risk factors for gastric cardia high-grade dysplasia in both men (BMI = 27.5–29.9: adjusted OR = 1.78, 95% CI = 1.02–3.10; BMI ≥ 30.0: adjusted OR = 2.54, 95% CI = 1.27–5.08) and women (BMI = 27.5–29.9: adjusted OR = 2.88, 95% CI = 1.27–6.55; BMI ≥ 30.0: adjusted OR = 2.77, 95% CI = 1.36–5.64), whereas only a BMI ranging from 27.5 to 29.9 was a risk factor for gastric noncardia high-grade dysplasia in both men (adjusted OR = 1.98, 95% CI = 1.25–3.14) and women (adjusted OR = 2.88, 95% CI = 1.43–5.81). In addition, higher serum total cholesterol was associated with an increased risk of gastric noncardia high-grade dysplasia (adjusted OR = 1.83, 95% CI = 1.25–2.69) in women. Increased BMI was associated with an increased risk of gastric high-grade dysplasia in both men and women, and higher serum total cholesterol increased the risk of gastric noncardia high-grade dysplasia in women. Abstract : Supplemental Digital Content is available in the text